2023
DOI: 10.33546/bnj.2750
|View full text |Cite
|
Sign up to set email alerts
|

Self-esteem among nursing students at a public university in Saudi Arabia: A cross-sectional study

Ahmed Mansour Almansour

Abstract: Background: Self-esteem is a subjective assessment of one’s own value and worth as a person. Self-esteem is recognized as an indicator of a person’s mental health, with lower levels associated with mental conditions such as stress and depression. In the context of nursing education, self-esteem has been linked to student’s academic performance, clinical competence, and overall well-being. Existing literature suggests that self-esteem among student nurses varies across countries and cultures. Assessing the self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 45 publications
0
0
1
Order By: Relevance
“…Similar to our findings, Shrestha et al (2018) indicated that 95.3% of nursing students reported good self-esteem, which is similar to our findings. However, this finding contradicts prior research that found students to have a moderate degree of self-esteem ( Almansour, 2023 ; Altaweel et al, 2023 ; Banappagoudar et al, 2022 ). This difference may be due to the fact that nursing students in Palestine face political challenges that differ from those in other countries, requiring them to be accountable and professional, which promotes their self-esteem and allows them to make fixed progress toward development and improvement.…”
Section: Discussioncontrasting
confidence: 91%
“…Similar to our findings, Shrestha et al (2018) indicated that 95.3% of nursing students reported good self-esteem, which is similar to our findings. However, this finding contradicts prior research that found students to have a moderate degree of self-esteem ( Almansour, 2023 ; Altaweel et al, 2023 ; Banappagoudar et al, 2022 ). This difference may be due to the fact that nursing students in Palestine face political challenges that differ from those in other countries, requiring them to be accountable and professional, which promotes their self-esteem and allows them to make fixed progress toward development and improvement.…”
Section: Discussioncontrasting
confidence: 91%